Horngren's accounting - NOBLES, Tracie; Brenda Mattison; Ella Mae Matsumara (New Jersey : Pearson, 2014)
Accounting presents the core content of the accounting course in a fresh format designed to help today's learners succeed. Built upon the foundation of the Horngren franchise, this new edition was created by an all-new author team who sought to bridge the gap between textbook content and classroom instruction techniques. New pedagogical features such as Instructor Tips & Tricks and Common Questions, Answered walk students through the material as a great instructor would, fostering deeper understanding of accounting theory and practice.
Includes index
Keywords: Accounting